NET N MINERALISATION IN COCONUT/NITROGEN FIXING TREE BASED SYSTEM - N.A Tennakoon; M. de S, Liyanage (International Coconut Community, 1997)
To study the net N mineralisation rates of coconut/NFT plantations, a field incubation technique was carried out. In this study, four types of NFT i.e. Acacia auriculiformis, Calliandra calothyrsus, Gliricidia sepium, Leucaena leucocephala and coconut monocropping were selected. Forty plastic tubes were inserted into the soil, to a depth of 15 cm at a distance of 2 m and l m away from coconut palm, for field incubation period of 2 weeks. Similarly another set of forty tubes were inserted for a 4 week field incubation period, after removing the previous set of tubes. Fresh soll samples (same depth) were also taken close to the inserted tubes on the day on which tubes were inserted for the estimation of initial N concentrations in the soil. Mineralised N concentrations were extracted by 2 M KCl and the net N mineralisation rates were calculated. Net N mineralisation was significantly higher (P= 0.001) 4 weeks after field incubation peniod than 2 weeks and also, the significant higher (P= 0.001) net N mineralisation was shown 2 m away from coconut than l m away from coconut. The highest net N mineralisation (4.9 ‑ 15.5 kgha-1) was found in Gliricidia site than in the other NFT sites, followed by Leucaena > Calliandra > Acacia. The lowest net N mineralisation (1.2 ‑ 2.2 kgha-1) was recorded in the coconut monocrop, either 2 weeks or 4 weeks incubation period. This study clearly indicated that growing NFTs with coconut enhances N availability in coconut lands and Gliricidia being the most promismig.